2022
DOI: 10.1037/edu0000760
|View full text |Cite
|
Sign up to set email alerts
|

Students’ personality and state academic self-concept: Predicting differences in mean level and within-person variability in everyday school life.

Abstract: A positive academic self-concept (ASC) relates to many desirable educational outcomes. Research on which student characteristics relate to the formation of ASC is therefore crucial. To examine the importance of personality for ASC, we investigated the relation between Big Five traits and mean level as well as within-person variability in state general-school ASC for the first time using intensive longitudinal data. The sample comprised N = 291 German ninth and 10th graders who completed a 3-week e-diary after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 89 publications
0
4
0
1
Order By: Relevance
“…These high correlations were subsequently confirmed through several studies [111,112,120,130,131]. Medium-to-low correlations have been reported for the association between ASC with CSN and NFC, but only small correlations have been uncovered between NFC and CSN [14,75,[132][133][134]. It has been shown that interests in different school subjects share many common elements with corresponding ASCs, up to a correlation of r Ø = 0.77 [13,27,[135][136][137].…”
Section: Redundanciesmentioning
confidence: 67%
See 1 more Smart Citation
“…These high correlations were subsequently confirmed through several studies [111,112,120,130,131]. Medium-to-low correlations have been reported for the association between ASC with CSN and NFC, but only small correlations have been uncovered between NFC and CSN [14,75,[132][133][134]. It has been shown that interests in different school subjects share many common elements with corresponding ASCs, up to a correlation of r Ø = 0.77 [13,27,[135][136][137].…”
Section: Redundanciesmentioning
confidence: 67%
“…An early meta-analysis that was conducted by Hansford and Hattie [10] revealed an average correlation of r Ø = 0.18 between overall (domain-general) self-concept and achievement, whereas self-concept of ability was more closely associated with achievement (r Ø = 0.42). The ASC, i.e., the way a person describes and evaluates his or her academic performance, is one of the most important motivational factors in education [11][12][13][14][15][16][17][18][19][20][21]. Until the 1970s, the ASC was often defined and measured without taking into account the differences between school subjects.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to improve students' awareness of employability skills and the needed experiences to develop these skills besides developing their understanding of their responsibility to improve their English language proficiency regarding both academic and social-communicative abilities to enhance their employability (Arkoudis et al, 2014). In addition, their self-awareness of their academic abilities, self-perception, and personal competencies represent motivational factors in their educational context (Hausen, et al, 2022). These personal competencies that contribute to self-perception and developing students" academic context include reasoning ability, intellectual curiosity, organization, responsibility, and sociability are among (Hausen, et al, 2022).…”
Section: Integrate Employability Skills In Language Coursesmentioning
confidence: 99%
“…In addition, their self-awareness of their academic abilities, self-perception, and personal competencies represent motivational factors in their educational context (Hausen, et al, 2022). These personal competencies that contribute to self-perception and developing students" academic context include reasoning ability, intellectual curiosity, organization, responsibility, and sociability are among (Hausen, et al, 2022).…”
Section: Integrate Employability Skills In Language Coursesmentioning
confidence: 99%
“…Xu & Zheng, 2022)、教育 (Hausen et al, 2023;Neubauer et al, 2022)、社会(Di Sarno et al, 2020Koval et al, 2019)、临床健康 (Gerstberger et al, 2023;van der Tuin et al, 2023;Wright et al, 2017)、组织管理(Reis et al, 2016Schmitt et al, 2017)等心理学领域的密集追踪研究中。 基于多层验证性因子分析的信度估计方法对 单维和多维测量结构的情况均适用, 本文以单维 测量结构的情况为例, 多维测量结构的情况可参 见以往相关研究 (Di Sarno et al, 2020;Neubauer et al, 2022;Wright et al, 2017)。当个体内和个体 ( ) 特性 (Mellenbergh, 1996;Wilkinson, 1999)…”
unclassified